2016
DOI: 10.1177/1524839915626413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Art Therapy to Heal the Effects of Trauma Among Refugee Youth

Abstract: This evaluation showed some effects of art therapy; however, symptom-focused assessment tools are not adequate to capture clients' growth resulting from the traumatic experience and this unique intervention. Future evaluations will benefit by using an art-based assessment and measuring posttraumatic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…Three of these provided objective assessment scores demonstrating symptom reduction (van Wyk et al 2012 ; Bolton et al 2014 ; Vukovich & Mitchell, 2015 ), though only one included a comparison group and locally validated measures (Bolton et al 2014 ). Two reports evaluated interventions aimed at symptom reduction in children (Rowe et al 2016 ). Two other child interventions focused on promoting wellbeing or post-traumatic growth, and did not include pre–post assessments to measure change (Prag & Vogel, 2013 ; Tanaka, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of these provided objective assessment scores demonstrating symptom reduction (van Wyk et al 2012 ; Bolton et al 2014 ; Vukovich & Mitchell, 2015 ), though only one included a comparison group and locally validated measures (Bolton et al 2014 ). Two reports evaluated interventions aimed at symptom reduction in children (Rowe et al 2016 ). Two other child interventions focused on promoting wellbeing or post-traumatic growth, and did not include pre–post assessments to measure change (Prag & Vogel, 2013 ; Tanaka, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rowe et al ( 2016 ) reported outcomes of the Burma Art Therapy Project, in which 30 refugees (age 11–20 years) from Myanmar living in the USA received an average of 16 sessions of art therapy, either individually or in groups, in schools over a 6-month period. Youth were assessed before and after the intervention using the Strengths and Difficulties Questionnaire, Hopkins Symptom Checklist, Harvard Trauma Questionnaire, and Piers–Harris Self-Concept Scale At baseline, 40% of participants met criteria for depression and 20% for anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Designed to tackle health disparities within the refugee population, refugee-focused health and social interventions typically center around community capacity-building, developing self-efficacy to navigate the U.S. healthcare system, and encouraging community empowerment (Baird et al, 2015;Glanz, Rimer, & Viswanath, 2008;Im & Rosenberg, 2016;Wieland et al, 2012). Despite an important foundation of public health social work research on refugee health education interventions, few interventions designed specifically for Burmese refugees have been implemented, and little to no program evaluations have been conducted to assess the feasibility and acceptability in delivery of these health education interventions for Burmese refugees living in the U.S. (Hartwig & Mason, 2016;Ornelas et al, 2017;Rowe et al, 2016;Walker, Koh, Wollersheim, & Liamputtong, 2015).…”
mentioning
confidence: 99%
“…Expressive Arts Therapy combines several of art such as visual arts, movement, drama, music, writing and other creative processes to foster personal growth and community development. Rowe, Watson-Ormond, English, Rubesin, Marshall, Linton, Amolegbe, Agnew-Brune, & Eng (2016) defined art therapy as psychotherapy which uses the art-making process to improve social, mental, and emotional well-being. This therapy can be implemented not only in individual counseling or group counseling, but also in family counseling.…”
Section: Introductionmentioning
confidence: 99%